Deep Insights into Data Analysis in Multi-Core Active Flash Arrays - Raju, P. J. R. Shalem; M., Prasad; Pokkuluri, Kiran Sree; Babu G., Ramesh; Varma, Ch. Phanendra; Kumar, K. Satish; P. B. V., Raja Rao (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Data analysis has become increasingly vital in the modern digital landscape, with organizations constantly seeking ways to extract valuable insights from their vast repositories of data. One emerging technology that has gained prominence is Multi-Core Active Flash Arrays (MCAFA), which combine the speed and parallel processing capabilities of flash storage with multiple processing cores to accelerate data-intensive workloads. This abstract provides an overview of the role of data analysis in MCAFA systems, highlighting the benefits and challenges associated with this innovative approach. Multi-Core Active Flash Arrays leverage a combination of high-performance flash storage and multiple CPU cores to deliver impressive computational power for data analysis tasks. These systems offer significant advantages over traditional storage arrays by reducing data access latency and increasing overall system throughput. As a result, they are well-suited for applications that demand real-time data processing and analysis, such as data analytics, machine learning, and scientific simulations.